The Effectiveness of the Contextual Virlab Practical Module on Energy Material on the Psychomotor Skills of Grade IV Students of Banyuripan Elementary School - Ziadatun Khoirunnisa; Suryandari Suryandari; Galih Albarra Shidiq; Ruwet Rusiyono; An-Nisa Apriani (DAS Institute, 2026)
The advancement of technology in education demands teachers to innovate learning processes, particularly to improve students' psychomotor skills. However, science learning for grade IV students still faces challenges such as limited innovation, minimal use of technology-based media, and unmeasured psychomotor skills. This study investigates the effectiveness of using a contextual Virtual Laboratory (VirLab) practicum module supported by PhET simulation in teaching energy material to fourth-grade students at Banyuripan Elementary School. Employing a quantitative pre-experimental design with a one-shot case study approach, this research involved 18 students who were observed during practicum activities focusing on imitation and manipulation stages of psychomotor skills. Data were analyzed using the normalized gain formula to measure skill improvement. Results revealed an average gain value of 0.8056, categorized as